Efek Penambahan Limbah Lokal Jerami Dan Sekam Padi Bagi Pertumbuhan Jamur Tiram Putih (Pleurotus ostreatus) - Shobah, Afifah Nur; Oktavia, Swastika (Universitas Muhammadiyah Surakarta, 2019)
White oyster mushroom (Pleurotus ostreatus) is a group of microscopic fungi that are used as food. P. ostreatus is cultivated in an artificial medium derived from sawdust and has been sterilized. However, the use of sawdust also has problems. Straw and husk of rice can be used as mushroom growing media because they contain organic ingredients such as cellulose, hemicellulose, and lignin. This study aimed to know the growth of white oyster mushroom (P. ostreatus) on straw and husk of rice as an artificial medium and to know the best composition of straw and husk of rice that can be got highly produced of white oyster mushroom (P. ostreatus). The methods of this research were experimental with ten treatments and included several stages including preparation of tools, materials and research sites, the stage of cultivation of P. ostreatus and data collection. This study used an experimental method with a completely randomized design consisting of 40 experimental units. The results obtained were the most optimal P. ostreatus mycelium growth in K1J2S1 treatment with a mean growth rate of 30,60 cm / 30 days, the highest wet weight was K3J1S0 which was 85,83 g while the highest dry weight was in K1J2S1 treatment that is equal to 8,71 g.